A multiscale air quality and health risk modelling system: Design and application over a local traffic management case study. (1st February 2023) - Silveira, Carlos; Ferreira, Joana; Miranda, Ana I.
Abstract: Air pollution is nowadays a serious public health problem worldwide, especially in urban areas, due to high population density and intense anthropogenic activity. This paper aims to present the development of a modelling tool suitable for simulating multiscale air quality and health impacts - the modair4health system, and its application to an urban case study. The modair4health system includes the online model WRF-Chem, which provides meteorological and air quality fields from regional to urban scales, and the computational fluid dynamics model VADIS, which uses the urban WRF-Chem outputs to simulate the flow and pollutant dispersion in urban built-up areas. A health module based on World Health Organization (WHO) methodologies was also integrated into the system to quantify physical and economic health impacts resulting from air quality changes. The system was applied over a local case study, which represents one of the busiest road traffic areas of the city of Coimbra in Portugal, to assess its operationality in estimating NO2 concentrations and health impacts, by testing two traffic management scenarios. This scenario analysis considered a 4-domain nesting approach, with the finer resolution (4 m) domain focusing on the local case study and on two simulation periods, for which short-term health impacts were estimated. Spatially, the air quality and health greatest benefits were simulated around roads, where higher emission reductions were estimated, but they were also strongly influenced by the urban structure, local weather and population affected. The modair4health system has revealed to be an important multiscale modelling tool for integrated air quality and health assessment, able to support decision makers by facilitating the choice of cost-effective air quality and health management strategies and decisions. Moreover, its user-friendly interface allows to quickly test other urban air pollution control policies and the easy adaptation and application to other case studies considering regional to local atmospheric influences. Graphical abstract: The modair4health multiscale modelling system is composed of two air quality models able to simulate atmospheric concentrations from regional/urban (WRF-Chem) to local (VADIS) scales, and a health module for estimating physical and economic health impacts caused by short and long-term human exposure to air pollutants. Image 1 Highlights: The developed modair4health modelling system is presented. It is able to simulate air quality and health impacts on multiple scales. The urban structure has a key role in flow variations and pollutant dispersion. Greater traffic scenario benefits are expected in areas and periods with higher NO2 . Integrated assessment tool to effectively support air pollution control policies.